Drying process, storage conditions, and time alter the biochemical composition and bioactivity of the anti-greenhouse seaweed Asparagopsis taxiformis - Regal, A.L. (2020)
The Azorean red seaweed Asparagopsis taxiformis may be used in human and animal diets. This seaweed is deemed to reduce the large production of methane—a major greenhouse gas—by ruminant digestion. Seaweed producers, however, have difficulties in ensuring a reliable and similar product throughout all year and in different years. Changes in biochemical composition and bioactivity are caused not only by natural variability, but also by the particular drying process, storage conditions, and storage time. Regarding the drying process, oven-dried samples had a lower EPA content, 1.9 ± 0.2% of the total FAs, than freeze-dried samples, 8.6 ± 1.7%. The same occurred with the phenolic contents and particularly with the ethanolic extracts. ABTS antioxidant activity results showed freeze-drying as advantageous. With respect to storage temperature, anti-inflammatory activity was higher in A. taxiformis at room temperature after three month storage. Moreover, EPA content in freeze-dried samples decreased to 0.3–1.0% after three month storage. Phenolic content in the ethanolic extracts also declined over storage time. In the case of aqueous extracts, however, variation was in the opposite direction. Antioxidant activity as measured by ABTS showed for almost all samples and types of extracts an increasing trend over time: from 0.26–1.75 to 0.75–4.40 mmol Trolox Eq/100 g dw. Anti-inflammatory activity increased over time from < 30% COX-2 inhibition at the beginning of the trial to > 30% COX-2 inhibition after three month storage. Therefore, there is a relevant bioactive potential in A. taxiformis and the drying process and storage conditions and time affect this potential